2018
DOI: 10.1080/1088937x.2018.1522382
|View full text |Cite
|
Sign up to set email alerts
|

Making the Arctic predictable: the changing information infrastructure of Arctic weather and sea ice services

Abstract: This paper explores the changing infrastructure around weather and sea ice information provisioning for Arctic marine areas. Traditionally, the most important providers of operational information on sea ice and weather conditions are the national sea ice and meteorological services. More recently, the community of Arctic information providers has become more heterogeneous with the establishment of numerous collaborative platforms. Three case studies will enhance our understanding of current developments (Baren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…As such, basic WWIC information is delivered as a public good, while more specialized services are typically distributed as a mix of public and private goods (Freebairn & Zillman, 2002). In the Polar Regions, NMHSs historically have a prominent role in observations and basic service delivery, but increased economic activities in the Polar Regions, particularly in the Arctic, have created a situation whereby specialized services are increasingly needed to ensure safe operations (Knol et al, 2018).…”
Section: Wwic Service Delivery In the Polar Regionsmentioning
confidence: 99%
“…As such, basic WWIC information is delivered as a public good, while more specialized services are typically distributed as a mix of public and private goods (Freebairn & Zillman, 2002). In the Polar Regions, NMHSs historically have a prominent role in observations and basic service delivery, but increased economic activities in the Polar Regions, particularly in the Arctic, have created a situation whereby specialized services are increasingly needed to ensure safe operations (Knol et al, 2018).…”
Section: Wwic Service Delivery In the Polar Regionsmentioning
confidence: 99%
“…There is an ongoing tension between standardization and differentiation of WWIC information services (see also Knol et al, 2018), between the production of these services and the communication with its users. Standardization tends to go hand in hand with increased automation of the production chain, which should give operational forecasters and sea-ice analysts more time to focus on specific areas where users need information on more detailed levels:…”
Section: Challenge 2: Automation As Blessing and Cursementioning
confidence: 99%
“…The marine Arctic is becoming more and more accessible to a wider range of users, including those involved in fisheries, marine tourism and shipping activities. The highly dynamic environments in which these actors operate call for a development of valuable weather, water, ice and climate information (WWIC) services (Dawson et al, 2017;Knol et al, 2018;Lamers, Duske, & van Bets, 2018). It is broadly acknowledged that user engagement is crucial for the development of such services (Hoke, Werner, Goessling, & Jung, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the PC now mandates that 'ships shall have the ability to receive up-to-date information including ice information for safe navigation' and requires a risk assessment methodology, POLARIS, to determine the limitations for ice operations (IMO, 2014). Ships will require more detailed sea-ice and weather information, encouraging numerous new ice information providers (Knol et al, 2018;Lamers, Duske, et al, 2018;Melia et al, 2016). However, navigating ice-covered areas requires both broad and precise knowledge of ice conditions depending on the region and type of activity.…”
mentioning
confidence: 99%
“…Previous studies identified services providing information and forecasts to support ice navigation and planning (Hamilton & Stroeve, 2016;Knol et al, 2018;Lovecraft et al, 2013). However, the rate of growth of users and information providers is potentially exceeding the understanding that is needed from both groups to work together effectively.…”
mentioning
confidence: 99%